Mitochondrial metabolism sustains DNMT3A-R882-mutant clonal haematopoiesis - Malgorzata Gozdecka; Monika Dudek; Sean Wen; Muxin Gu; Richard J. Stopforth; Justyna Rak; Aristi Damaskou; Guinevere L. Grice; Matthew A. McLoughlin; Laura Bond; Rachael Wilson; George Giotopoulos; et al. (Nature, 2025)
Abstract Somatic DNMT3A-R882 codon mutations drive the most common form of clonal haematopoiesis (CH) and are associated with increased acute myeloid leukaemia (AML) risk1,2. Preventing expansion of DNMT3A-R882-mutant haematopoietic stem/progenitor cells (HSPCs) may therefore avert progression to AML. To identify DNMT3A-R882-mutant-specific vulnerabilities, we conducted a genome-wide CRISPR screen on primary mouse Dnmt3a R882H/+ HSPCs. Among the 640 vulnerability genes identified, many were involved in mitochondrial metabolism, and metabolic flux analysis confirmed enhanced oxidative phosphorylation use in Dnmt3a R882H/+ versus Dnmt3a +/+ (WT) HSPCs. We selected citrate/malate transporter Slc25a1 and complex I component Ndufb11, for which pharmacological inhibitors are available, for downstream studies. In vivo administration of SLC25A1 inhibitor CTPI2 and complex I inhibitors IACS-010759 and metformin suppressed post-transplantation clonal expansion of Dnmt3a R882H/+, but not WT, long-term haematopoietic stem cells. The effect of metformin was recapitulated using a primary human DNMT3A-R882 CH sample. Notably, analysis of 412,234 UK Biobank participants showed that individuals taking metformin had a markedly lower prevalence of DNMT3A-R882-mutant CH, after controlling for potential confounders including glycated haemoglobin, diabetes and body mass index. Collectively, our data propose modulation of mitochondrial metabolism as a therapeutic strategy for prevention of DNMT3A-R882-mutant AML.